Online lectures with local wisdom context: efforts to develop students’ higher-order thinking skills - Hikmawati Hikmawati; I Wayan Suastra; Ketut Suma; A. A. Istri Agung Rai Sudiatmika (International Journal of Evaluation and Research in Education (IJERE), 2024)
Indonesian students have low higher-order thinking skills (HOTS), so efforts are needed to improve these skills. This research aims to examine the effect of online learning with local wisdom context on students’ HOTS. The online learning in question is a lecture using Zoom Cloud Meeting (ZCM), Google Meet (GM), and a combination of GM and learning management system (LMS) SPADA Universitas Mataram. This study took a sample of 77 5th-semester students who took the 2021/2022 Physics Curriculum Study course at Universitas Mataram, Indonesia. This quantitative research method uses a posttest-only group design. The student HOTS data were obtained based on the essay test after the treatment. The data analysis used to test the research hypothesis is one-way ANOVA with calculations using the SPSS 25 application. The research results showed that the class combining GM and SPADA UNRAM with local wisdom context significantly affects students’ HOTS scores. The average score of HOTS with the lecture model is the highest compared to the other two classes. Thus, online lectures with local wisdom context using a combination of GM and SPADA UNRAM can be an effort to develop HOTS for prospective physics teacher students.